Endocrine and molecular investigations in a cohort of 25 adolescent males with prominent/persistent pubertal gynecomastia. (4th February 2016) - Paris, F.; Gaspari, L.; Mbou, F.; Philibert, P.; Audran, F.; Morel, Y.; Biason‐Lauber, A.; Sultan, C.
Summary: Pubertal gynecomastia is a common condition observed in up to 65% of adolescent males. It is usually idiopathic and tends to regress within 1–2 years. In this descriptive cross‐sectional study, we investigated 25 adolescent males with prominent (>B3) and/or persistent (>2 years) pubertal gynecomastia (P/PPG) to determine whether a hormonal/genetic defect might underline this condition. Endocrine investigation revealed the absence of hormonal disturbance for 18 boys (72%). Three patients presented Klinefelter syndrome and three a partial androgen insensitivity syndrome (PAIS) as a result of p.Ala646Asp and p.Ala45Gly mutations of the androgen receptor gene. The last patient showed a 17α‐hydroxylase/17, 20‐lyase deficiency as a result of a compound heterozygous mutation of the CYP17A1 gene leading to p.Pro35Thr(P35T) and p.Arg239Stop(R239X) in the P450c17 protein. Enzymatic activity was analyzed: the mutant protein bearing the premature stop codon R239X showed a complete loss of 17α‐hydroxylase and 17, 20‐lyase activity. The mutant P35T seemed to retain 15–20% of 17α‐hydroxylase and about 8–10% of 17, 20‐lyase activity. This work demonstrates that P/PPG had an endocrine/genetic cause in 28% of our cases. PAIS may be expressed only by isolated gynecomastia as well as by 17α‐hydroxylase/17, 20‐lyase deficiency. Isolated P/PPG is not always a 'physiological' condition and should thus be investigated through adequate endocrine and genetic investigations, even though larger studies are needed to better determine the real prevalence of genetic defects in such patients.